Exploring MOOC acceptance and readiness among postgraduate students at a higher learning institution - Tahiru, Mukaramatu; Kamalludeen, Rosemaliza (IIUM Press, 2018)
This study explores the acceptance of massive open online courses among postgraduate students in a higher learning institution in Malaysia, and their readiness to use it for learning. Acceptance in this context refers to actual use, intention to use the platform for academic purposes and their attitude towards it, while readiness refers to their knowledge of MOOCs and perceptions of its usefulness. One hundred and ninety postgraduate students responded to the survey (N = 190). The data analysis used descriptive statistics, i.e. frequencies, percentages, means and standard deviations. The findings reveal that a majority of postgraduate students did not have knowledge of MOOCs, and very few had any actual usage of MOOCs. However, most demonstrated a positive attitude towards MOOCs and expressed an intention to use the platform for academic purposes. The findings highlighted how higher learning institutions ought to scheme policies to increase students' awareness of MOOCs and understanding of its usefulness, hence improving their acceptance and readiness to use the platform.